Nitrogen management schedule for Bt cotton under different planting geometries in semi-arid north-western plains of India - Kaur, Ramanjit; Dass, Anchal; Verma, V.P (Annals of Agricultural Research, 2016)
Cotton occupies a predominant position amongst all cash crops in India. However, the full proof agronomic practices are still lacking, particularly for Bt. cotton. Therefore, a field experiment was conducted at research farm of ICAR-IARI, New Delhi during kharif seasons of 2013 and 2014 to determine precise nitrogen (N) application rate and planting geometries for Bt. Cotton. The treatments consisted of four planting geometries viz., 75 × 60 cm (R), 75 × 45 cm, 60 × 45 cm and 90 × 60 cm and five N-application methods viz., recommended dose of N (RDN), site specific nutrient management using SPAD meter (SPAD index <35), (SSNM), soil test crop response (STCR) approach (140 kg/ ha), GreenSeeker (0.67 NDVI) and N-rich strip. The results showed that the highest seed cotton yield (2.13 t/ha) was recorded in N-rich strip where 25 kg N/ha more N was applied as compared to the RDN and this treatment was successively followed by the treatment where N was applied at NDVI 0.67 (2.01 t/ha) and these two treatments were statistically at par with each other. Among different planting geometries studied, the highest seed cotton yield, leaf area, leaf area index, dry matter, number of bolls/plant, number of sympodial branches plant-1 were recorded with 75 × 60 cm planting geometry. Thus SPAD meter and GreenSeeker aided site specific N application and planting spacing 75 × 60 cm can be adopted for improving Bt. cotton productivity in the northwestern plains of India.